ASSESSMENT OF SILVER NANOPARTICLE-INDUCED MORPHOLOGICAL, BIOCHEMICAL AND PHYSIOLOGICAL ALTERATIONS IN WHEAT ROOTS - VARDAR, FİLİZ (UNIV STUDI ROMA LA SAPIENZA, 2019)
Silver nanoparticle (Ag NP) is one of the most widely used nanoparticles in consumer products due to its antimicrobial properties. The wide usage of Ag NPs has led to their increased release into the environment and it may affect plants physiological and biochemical functions. Therefore, this study has been performed to reveal the dose-dependent (0, 0.5, 1, 5, 10 and 20 ppm) effects of 10-nm-sized Ag NPs on wheat (Triticum aestivum) roots after 15 d, correlating with the appearance of various biochemical and physiological stress responses. The effects of Ag NPs were examined using different experiment such as root elongation, uptake of Ag NPs, TEM analysis, lignin accumulation, callose deposition, H2O2 content, lipid peroxidation, activities of non-enzymatic and enzymatic antioxidants. The result showed that 10 nm-sized Ag NPs caused the inhibition of root elongation over 5 ppm. dose-dependent accumulation of Ag+, ultrastructural changes, lignin accumulation, callose deposition, increase of H2O2 content and lipid peroxidation and SOD, CAT, GPOX, APOX and GR enzymes activities altered as compared to control. As a result, 0.5 and 1 ppm Ag NPs demonstrated hormetic response, but over 5 ppm reduced plant root growth inducing the plant antioxidant defence systems.
Keywords: SILVER NANOPARTICLES; WHEAT; BIOACCUMULATION; CALLOSE; LIGNIN; ROS; ANTIOXIDANT DEFENSE; CERIUM OXIDE NANOPARTICLES; GLUTATHIONE-REDUCTASE; SUPEROXIDE-DISMUTASE; ENZYME-ACTIVITIES; TOXICITY; PEROXIDASE; ALUMINUM; EXPOSURE; PROLINE; GROWTH